2011
DOI: 10.1007/s12020-011-9515-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing loss in patients with Graves’ disease

Abstract: Hearing loss has commonly been reported in association with thyroid disorders and during treatment with propylthiouracil. The relationship between hyperthyroidism and the auditory system has not been previously investigated. The aim of this cross-sectional, case-control study was to investigate hearing loss in patients with Graves' disease (GD). The study population consisted of patients with newly diagnosed GD and healthy controls. Pure tone audiometry at frequencies of 250, 500, 1000, 2000, 4000 and 8000 Hz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
2
24
0
1
Order By: Relevance
“…Moreover, studies have indicated that thyroid dysfunction is related to hypercoagulability and venous thrombosis, which may impair the cochlear circulation, thus causing SSNHL [28,29]. Impaired hearing ability has been reported in patients with autoimmune-related hyperthyroidism, particularly at high frequencies [30]. Both subclinical and overt hyperthyroidism modified the coagulation-fibrinolytic balance and induced a prothrombotic state [31,32], which may also have increased the risk of SSNHL [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have indicated that thyroid dysfunction is related to hypercoagulability and venous thrombosis, which may impair the cochlear circulation, thus causing SSNHL [28,29]. Impaired hearing ability has been reported in patients with autoimmune-related hyperthyroidism, particularly at high frequencies [30]. Both subclinical and overt hyperthyroidism modified the coagulation-fibrinolytic balance and induced a prothrombotic state [31,32], which may also have increased the risk of SSNHL [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…No study could be found in the literature reporting comparison between hypothyroidism and hyperthyroidism on extended high frequency hearing sensitivity. However, Berker et al [13] studied 22 subjects with Grave's disease had also reported sensorineural hearing loss especially at higher frequency in the majority of the subjects. [13] The auditory brainstem evoked response audiometry showed significant difference for absolute latency of wave I and III in both ears and wave V for right ear.…”
Section: Discussionmentioning
confidence: 99%
“…However, Berker et al [13] studied 22 subjects with Grave's disease had also reported sensorineural hearing loss especially at higher frequency in the majority of the subjects. [13] The auditory brainstem evoked response audiometry showed significant difference for absolute latency of wave I and III in both ears and wave V for right ear. Karlos & Chandrasekhar et al [12,20] have also reported the increased absolute latencies of waves that might be due to decreased metabolism of tissues which may result in slow conduction of periphery and poor recruitment of neuronal pool of the generators of the waves in brainstem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Exact mechanisms are yet to be elucidated. There have also been reports of ototoxicity secondary to ANCA-positive vasculitis in patients treated with propylthiouracil, which manifests as sensorineural hearing loss.…”
Section: Hearing and Thyroid-parathyroid Disordersmentioning
confidence: 99%